Fine structure of the alimentary canal of the larval blow fly Chrysomya megacephala (Diptera: Calliphoridae) - Boonsriwong W. (2014)
Morphology of the alimentary canal of the mature third instar larva of the blow fly, Chrysomya megacephala (F.), was examined using light, scanning, and transmission electron microscopy. Salivary structures consist of a single median deferent duct that bifurcates into efferent ducts connected to paired, tubular salivary glands comprised of closely packed conical-shaped epithelial cells with large nuclei. The crop occurs as a large, swollen diverticulum of the digestive tube and is lined internally with convoluted cuticle (epicuticle and endocuticle). The esophagus is a simple, straight tube internally lined with cuticle and externally encompassed by muscle fibers. The cardia is a bulb-like structure composed of anterior foregut tissue and posterior midgut tissue from which the peritrophic membrane (PM) is produced. The midgut begins within the cardia which is flanked posteriorly by four tubular gastric caeca that are lined internally with four to five layers of cuboidal epithelial cells bearing microvilli. Midgut tissue is lined with simple cuboidal epithelium whose cells are filled with numerous secretory granules and possessed long microvilli facing the lumen. A peritrophic membrane is contained within the midgut lumen. The larval hindgut consists of the pylorus, Malpighian tubules, ileum, colon, rectum, and anus, posteriorly. The pylorus is characterized by a single layer of epithelial cells encircled by a muscular layer and the presence of PM within the lumen. Malpighian tubules each diverge into two tubular structures totalling four long tubules of long chained cuboidal cells bearing microvilli internally. The wall of the ileum is comprised primarily of a monolayer of cuboidal epithelial cells with large oval nuclei and more intense muscular fibers surrounding the periphery. A cuticular layer surrounds the lumen containing the PM. This inner cuticle consists of a thin epicuticle that is electron-dense; whereas, the endocuticle is much thicker but less electron-dense. Myo-epithelial cells are dense in the anal region, where the PM persists. © 2006 Springer-Verlag.